Photocatalytic Homocoupling Transformations - de Gracia Retamosa, María; Döndaş, Haci Ali; Sobhani, Sara; Nájera, Carmen; Yus, Miguel A.; Sansano, José M. (Synthesis, 2021)
Homocoupling reactions promoted by photocatalysts are not very abundant in the literature. However, the products generated from such processes are very interesting. In this review, we highlight the most relevant reports concerning photocatalyzed dimerizations covering the literature until the middle of 2020. Reactions will be classified according to the type of starting material employed, with an emphasis being placed on the corresponding mechanism. 1 Introduction2 Arenes and Heteroarenes3 Alkenes4 Alkanes5 Alkynes6 Aldehydes, Ketones, Alcohols, Amines and Imines7 Carboxylic Acids8 Nitro Compounds9 Conclusions
Keywords: photocatalysis; photoredox; sensitizers; homocoupling; dimerization